Strategies For The Internationalization Of Spice Smes Through Exports: A Case Study Of PT Adore Rempah Indonesia - Arif Wicaksono; Sudarmiatin; Heri Pratikno (Citakonsultindo, 2026)
This study aims to analyze the internationalization strategies of micro, small, and medium-sized enterprises (MSMEs) in the spice sector through export mechanisms, using PT Adore Rempah Indonesia as a case study. The study employs a qualitative approach using the case study method. Data collection was conducted through in-depth interviews, field observations, and documentation related to production processes, quality control, packaging, and the management of international market networks. Data analysis was performed descriptively using the Uppsala Model and the Resource-Based View perspectives. The results indicate that the success of a company’s internationalization strategy is influenced by several key factors: consistent product quality, strengthening partnerships within the supply chain, implementing product differentiation, and holding certifications that support international trade standards. Additionally, the internationalization process occurs gradually through market learning, adaptation to the needs of international buyers, and the development of global business networks. The research findings confirm that the integration of internal resource strengths, product innovation, and compliance with international standards is a key factor in enhancing the competitiveness of spice SMEs in the global market. This study implies that strengthening production capacity, improving product quality, and developing international partnership networks should be key strategies in promoting the sustainability of SME exports in the spice sector.